Posture-invariant myoelectric control with self-calibrating random forests - Jiang, Xinyu; Ma, Chenfei; Nazarpour, Kianoush (Frontiers in Neurorobotics, 2024)
IntroductionMyoelectric control systems translate different patterns of electromyographic (EMG) signals into the control commands of diverse human-machine interfaces via hand gesture recognition, enabling intuitive control of prosthesis and immersive interactions in the metaverse. The effect of arm position is a confounding factor leading to the variability of EMG characteristics. Developing a model with its characteristics and performance invariant across postures, could largely promote the translation of myoelectric control into real world practice.MethodsHere we propose a self-calibrating random forest (RF) model which can (1) be pre-trained on data from many users, then one-shot calibrated on a new user and (2) self-calibrate in an unsupervised and autonomous way to adapt to varying arm positions.ResultsAnalyses on data from 86 participants (66 for pre-training and 20 in real-time evaluation experiments) demonstrate the high generalisability of the proposed RF architecture to varying arm positions.DiscussionOur work promotes the use of simple, explainable, efficient and parallelisable model for posture-invariant myoelectric control.